Smart Synthesis of High-Performance Thermosets Based on ortho-Amide–Imide Functional Benzoxazines - Zhang, Kan; Ishida, Hatsuo (Frontiers in Materials, 2015)
High performance thermosets via amide-imide functional benzoxazine resins as precursors have been synthesized. The structures of synthesized monomers have been confirmed by 1H NMR and FT-IR. Among these two benzoxazine monomers, the ortho-amide-imide functional benzoxazine resin shows powerful features both in the synthesis of benzoxazine monomers and the properties of the corresponding thermosets. For the cross-linked poly(amide-co-imide) based on ortho-amide-imide functional benzoxazine, a smart route is adopted to develop a more thermally stable cross-linked poly(benzoxazole-co-imide). Besides, the poly(benzoxazole-co-imide) can also undergo a further thermal treatment to form polybenzoxazole. Furthermore, a main-chain type ortho-functional polybenzoxazine with amide-co-imide and benzoxazine groups as repeating units has also been prepared. Both the ortho-amide-imide functional benzoxazine and main-chain type polybenzoxazine resins show the possibility to form high performance thermosets with low cost and easy processability .